RESPOSTAS FISIOLÓGICAS E AGRONÔMICAS DA CULTURA DA BATATA EM FUNÇÃO DO ESPAÇAMENTO ENTRE PLANTAS E ÉPOCAS DE AMONTOA - Sales, Lívia Luiza Souza Rezende (2011)
The potato has great economic importance, especially intensively in the Brazilian agriculture. The State of Paraná, although not present higher productivity has one of the largest potato-growing areas, and the Midwest Paranaense (Campos Guarapuava), has stood for quality and yield of tubers. This fact is credited to the regional climate and soil characteristics conducive to the growth, coupled with the introduction and constant search for new production technologies, proper planting dates, among others. However, faced with rising production costs and potential gains in productivity and quality, it is necessary to generate information that subsidize the best technical decisions, particularly with regard to crop management. In particular, ridging and row spacing has great influence in the formation and tuber yield. Thus, the objective was to evaluate the effect of different times of piles and plant spacing on yield and quality of tubers of cultivar Agata. For this, an experiment was conducted in the area of the Department of Agronomy, State University of West Center, UNICENTRO Campus CEDETEG, Guarapuava - PR. We used a randomized experimental design in a 4 x 4 replicates, comprising four different times of ridging (ridging in the planting, at 10 DAE, 20 DAE and without ridging), and four plants in the row spacing (16 , 22, 28 and 34 cm). It was found that the studied factors had an effect on morphological characteristics of the culture, changing the length of the longest main stem and leaf area index, and on production traits, which shows that the smaller spacing of cultivation tend to result in composite production tubers of smaller size, but in greater numbers, as opposed to that seen in greater spacing where the outcome of production is composed of tubers larger and fewer in number. Heaping up time demonstrates that this practice after the emergence of the plants affect plant growth and crop production, notably being more suitable managements ridging at planting or without completion of the lumps that cause better production results, considering both productivity and the size of tubers produced.